A Dynamic Survival Modeling Approach to the Prediction of Web Survey Breakoff. (12th June 2021) - Mittereder, Felicitas; West, Brady T
Abstract: Respondents who break off from a web survey prior to completing it are a prevalent problem in data collection. To prevent breakoff bias, it is crucial to keep as many diverse respondents in a web survey as possible. As a first step of preventing breakoffs, this study aims to understand breakoff and the associated response behavior. We analyze data from an annual online survey using dynamic survival models and ROC analyses. We find that breakoff risks between respondents using mobile devices versus PCs do not differ at the beginning of the questionnaire, but the risk for mobile device users increases as the survey progresses. Very fast respondents as well as respondents with changing response times both have a higher risk of quitting the questionnaire, compared to respondents with slower and steady response times. We conclude with a discussion of the implications of these findings for future practice and research in web survey methodology.